Tweeting democracy: X and political participation of Indonesian youth - Anwar, Rully Khairul; Khadijah, Ute Lies Siti; Lusiana, Elnovani (Faculty of Communication Sciences Universitas Padjadjaran, 2024)
The rise of social media has undeniably improved engagement, politics, and communication. The emergence of X has revolutionized political conversations and strengthened the political engagement of both citizens and politicians. It is crucial that we conduct a thorough examination of the importance of this phenomenon, particularly in the Indonesian context. This study aims to delve into the role of X in shaping political participation among Indonesian youth. The study was conducted among three hundred male and female students from five prestigious universities in West Java, Indonesia: UNPAD, ITB, UPI, UIN, IPB, and Telkom University. For data collection, the researcher used a quantitative method in which closed-ended questionnaires were distributed. In addition, the researcher also conducted interviews with randomly selected respondents to ask them about their experiences with X. This study shows that X greatly influences young people and plays an important role in teaching political awareness. X impacts young people by helping them gain knowledge about fundamental political rights. The results also show that messages on X influence respondents’ political orientation and help them decide who to vote for in elections. In addition, the study shows that X has become an excellent source to connect political leaders with their constituents. By analyzing the approaches of political leaders and young people behind the use of X, this study contributes to future research on political influence on social media, especially X.